Analisis Sistem Permintaan Beras Pasar Tradisional Perspektif Ekonomi Islam (Studi Pada Pasar Wirolegi Jember) - Kholifah, Nur; Hidayah, Siti; Sugiarto, Riki (LAN TABUR : Jurnal Ekonomi Syariah, 2023)
In micro economic studies, the discussion is based on individual behavior as economic actors whose task is to determine price levels in the market mechanism process. The market mechanism itself is an interaction between demand from consumers and supply from producers, so that the price formed is a combination of the strengths of each party. This research uses descriptive qualitative research by examining conditions in the field which will then be analyzed based on observation data. Based on the results of the analysis of the rice demand system in traditional markets by considering the factors that influence it and the results of data collection, it can be seen that the demand for rice in Jember Regency is still very high. This is proven by the enthusiastic response of the community during market operations carried out by the Jember Regency Industry and Trade Department In micro economic studies, the discussion is based on individual behavior as economic actors whose task is to determine price levels in the market mechanism process. The market mechanism itself is an interaction between demand from consumers and supply from producers, so that the price formed is a combination of the strengths of each party. This research uses descriptive qualitative research by examining conditions in the field which will then be analyzed based on observation data. Based on the results of the analysis of the rice demand system in traditional markets by considering the factors that influence it and the results of data collection, it can be seen that the demand for rice in Jember Regency is still very high. This is proven by the enthusiastic response of the community during market operations carried out by the Jember Regency Industry and Trade Department